Financial performance of English NHS trusts and variation in clinical outcomes: a longitudinal observational study - Nagendran, Myura (BMJ Open, 2019)
OBJECTIVES: To examine the association between financial performance as measured by operating margin (surplus/deficit as a proportion of turnover) and clinical outcomes in English National Health Service (NHS) trusts. SETTING: Longitudinal, observational study in 149 acute NHS trusts in England between the financial years 2011 and 2016. PARTICIPANTS: Our analysis focused on outcomes at individual NHS Trust-level (composed of one or more acute hospitals). PRIMARY AND SECONDARY OUTCOMES: Outcome measures included readmissions, inpatient satisfaction score and the following process measures: emergency department (Accident and Emergency (A&E)) waiting time targets, cancer referral and treatment targets and delayed transfers of care (DTOCs). RESULTS: There was a progressive increase in the proportion of trusts in financial deficit: 22% in 2011, 27% in 2012, 28% in 2013, 51% in 2014, 68% in 2015 and 91% in 2016. In linear regression analyses, there was no significant association between operating margin and clinical outcomes (readmission rate or inpatient satisfaction score). There was, however, a significant association between operating margin and process measures (DTOCs, A&E breaches and cancer waiting time targets). Between the best and worst financially performing Trusts, there was an approximately 2-fold increase in A&E breaches and DTOCs overall although this variation decreased over the 6 years. Between the best and worst performing trusts on cancer targets, the magnitude of difference was smaller (1.16 and 1.15-fold), although the variation slowly rose during the 6 years. CONCLUSIONS: Operating margins in English NHS trusts progressively worsened during 2011–2016, and this change was associated with poorer performance on several process measures but not with hospital readmissions or inpatient satisfaction. Significant variation exists between the best and worst financially performing Trusts. Further research is needed to examine the causal nature of relationships between financial performance, process measures and outcomes.